Otonomi Daerah dan Pertumbuhan Ekonomi di Indonesia: Literature Review - Bahasoan, Awal Nopriyanto; Anwar, Anas Iswanto; Lekas, Meldilianus Nabas J; Asryad, Rahmat (Ekonomis: Journal of Economics and Business, 2024)
This article aims to conduct a literature review regarding the relationship between regional autonomy and economic growth in Indonesia. Through searching the literature from several sources, this article finds that there is debate about whether regional autonomy can accelerate or inhibit economic growth. However, the majority of studies show that regional autonomy has a positive impact on economic growth, especially when local governments are able to manage resources effectively and efficiently and have a significant influence on economic growth in Indonesia. Therefore, efforts are needed to improve the quality of human resources and infrastructure in the regions, so as to increase the effectiveness of the management of existing resources.